Pengaruh Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Sepatu Merek Converse - Rini Astuti; Isna Ardila; Rodhitur Rahman Lubis (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
Promotion and Product Quality are important things that can influence purchasing decisions, the better the quality of the products that are owned and supported by attractive and persuasive promotions, it will be able to provide encouragement to consumers in making purchasing decisions on marketed products. This study aims to determine whether there is an effect of promotion on purchasing decisions, and whether there is an effect of product quality on purchasing decisions and whether there is an effect of promotion and product quality on purchasing decisions for Converse products on UMSU students. The population in this study were all UMSU students. Sampling in this study using the Slovin formula with the results of 100 respondents who became the sample. The data analysis technique used multiple linear regression, classical assumption test, t test, f test, and coefficient of determination. The results of this study indicate that the promotion variable has a significant effect on purchasing decisions, and the variable quality of the product has a significant effect on purchasing decisions. Based on the simultaneous test, promotion variables and product quality have a significant effect on purchasing decisions.